استثمار الأملاك الوقفية عن طريق الايجار - أ زيدي, يوب (جامعة الوادي -University eloued, 2022)
يعتبر الوقف من أهم المؤسسات الخيرية والاقتصادية التي عرفتها الإنسانية، باعتبار أحد الصيغ الإنسانية العريقة وهو نظام قديم جدا لكنه كان محصورا في أماكن العبادة ويحظر التصرف في الرقبة وتوجيه المنفعة لجهة معلومة في الحضارات القديمة وقد خصص جزء صغير منه للفقراء والمساكين، وبمجئ الإسلام تطور أصبح الوقف أحد مظاهر الحضارة، حيث عرف نقلة نوعية و ذلك بسبب حث الإسلام على الإنفاق وفعل الخير مصداقا لقوله تعالى ¯لن تنالوا البر حتى تنفقوا مما تحبون وما تنفقوا من شيء فإن الله به عليم ¯.، فقد تعددت أغراض الوقف وتنوعت أهدافه، وانتقل من الصعيد الديني إلى الصعيد الاجتماعي وأصبح له اهتمام خاص ومكانة سامية تليق به حيث وجدوا له منافذ أخرى لتوسيع مجالاته كافة وب ذلك يتوسع الاستغلال الوقفي إلى مجالات أكبر تحقق الاستغلال العام ولكن وبطرق قانونية وفق ما تنص عليه قوانين استغلال الملك الوقفي وبهذا توسع مفهوم الوقف إلى مجال الاستثمار الذي يرمي إلى التنمية الاقتصاديةThe endowment is considered one of the most important charitable and economic institutions known to humanity, considering it is one of the ancient human formulas, and it is a very old system, but it was confined to places of worship and it was forbidden to dispose of the neck and direct the benefit to a known destination in ancient civilizations, and a small part of it was allocated to the poor and needy, and with the advent of Islam, the endowment became developed. One of the manifestations of civilization, where he knew a qualitative leap due to Islam's urging to spend and do good, in accordance with the Almighty's saying ¯ You will not attain righteousness until you spend from what you love and whatever you spend, God is All-Knowing of it. To the social level, it has a special interest and a lofty position worthy of it, as they found other outlets for it to expand all its fields. Thus, the endowment exploitation expands to larger areas that achieve general exploitation, but through legal methods, according to the laws of the exploitation of the endowment property, and thus the concept of the endowment expanded to the field of investment that aims To economic development, they gave this endowment an economic face, and for the first time in human history they established long-term economic institutions, based on the principle of community service, in a form that is more like We are what are called today civil society institutions.
ماستر عقاري
Keywords: الاستثمار/ الأملاك الوقفية/ الايجار/ المؤسسات الخيرية; Investment / endowment properties / rent / charitable institutions